2020
DOI: 10.1093/humrep/dez273
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the scope of in vitro maturation for fertility preservation: transvaginal retrieval of immature oocytes during endoscopic gynaecological procedures

Abstract: STUDY QUESTION Could in vitro maturation (IVM) following transvaginal oocyte retrieval during gynaecological surgery (IVM-surgery) be an effective and safe strategy for fertility preservation? SUMMARY ANSWER IVM-surgery on unstimulated ovaries is a novel option that can be considered for fertility preservation for women requiring gynaecological surgery, but more research is needed to identify appropriate patients who may bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Clinical pregnancy was defined as the ultrasound visualization of at least one gestational sac on 30 days after ET. Live birth was defined as the delivery of at least one newborn, irrespective of the gestation (Song et al, 2020). Clinical outcomes of embryo transfer cycles were measured by clinical pregnancy rate per cycle (CPR, the number of cycles achieving clinical pregnancy/the number of embryo transfer cycles), cumulative clinical pregnancy rate (CCPR, the number of patients achieving clinical pregnancy/the number of patients undergoing at least one embryo transfer cycle), live birth rate per cycle (LBR, the number of cycles achieving live birth/the number of embryo transfer cycles), cumulative live birth rate (CLBR, the number of patients achieving live birth/the number of patients undergoing at least one embryo transfer cycle).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical pregnancy was defined as the ultrasound visualization of at least one gestational sac on 30 days after ET. Live birth was defined as the delivery of at least one newborn, irrespective of the gestation (Song et al, 2020). Clinical outcomes of embryo transfer cycles were measured by clinical pregnancy rate per cycle (CPR, the number of cycles achieving clinical pregnancy/the number of embryo transfer cycles), cumulative clinical pregnancy rate (CCPR, the number of patients achieving clinical pregnancy/the number of patients undergoing at least one embryo transfer cycle), live birth rate per cycle (LBR, the number of cycles achieving live birth/the number of embryo transfer cycles), cumulative live birth rate (CLBR, the number of patients achieving live birth/the number of patients undergoing at least one embryo transfer cycle).…”
Section: Methodsmentioning
confidence: 99%
“…For patients with anti-mullerian hormone (AMH) < 5 ng/ml, laparoscopic ovarian drilling is not considered. As this study was conducted based on a finished prospective cohort study, detailed information can be found in XL Song's study (8).…”
Section: Transvaginal Oocyte Retrieval and Gynecological Surgerymentioning
confidence: 99%
“…After 7 days of progesterone treatment, one blastocyst was transferred into the uterine. Detailed information can be found in XL Song's study (8).…”
Section: Frozen-thawed Embryo Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Immature oocytes collection and in vitro maturation are techniques with multiple potential indications: Patients at risk of ovarian hyperstimulation (OHSS) or with Polycystic Ovary Syndrome (PCOS); women that underwent invasive surgery; patients at risk of exposure to estrogens; oocyte donation program; optimization of stimulated cycles; classic in vitro fertilization (IVF) or assisted by intracytoplasmic sperm microinjection (ICSI), and fertility preservation for social reasons or cancer patients [26][27][28]. In this last group, patients for oocyte vitrification and ovarian cortex preservation are included.…”
Section: Introductionmentioning
confidence: 99%